Elemen Estetis Sendratari Manarajang Lawok pada Pertunjukan Launching Calendar of Charming Event Palembang Tahun 2022 - Rully Rochayati; Dewi Purwaningsari; Nita Maelatul Hasanah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this paper is to find out how the aesthetic elements contained in the Manarajang Lawok ballet. The problem is focused on the aesthetic elements of choreography. In order to approach this problem, a theoretical, a theoretical reference from Y. Sumandiyo Hadi was used in 2012 with the title choreography (From-Engineering-Content). The data were collected throuhg data triangulation and analyzed qualitatively. This study concludes that the manarajang lawok ballet is a new creation, dance by 10 dancers. The Manarajang Lawok ballet is discussed in 3 aesthetic elements of choreography, namely the concept of motion as an aesthetic element of choreography, namely the movements performed by dancers are focussed in such away as to make it look epic when performed. The conceptof space as an aesthetic choreography element which is further divided into positive-negative space discussions, levels using low, medium and high levels, floor patterns using locomotor movement, stasionary and pause, directions using the eight cardinal directions, dimensions which includes height, width and depth. It is also discussed in the concept of time as an aesthetic element of choreography, which is divided into three parts, aspects of the tempo of the fast and slow movements performed by the dancers, the aspect of rhythm, namely the strenght and softness of the movements performed, and the duration, which is 11 minutes 40 seconds.